Nexus requirements for taxation of non-residents' business income : a normative evaluation in the context of the global economy - Gadžo, Stjepan (Doctoral series, 2018)
This book contains a critical evaluation of the nexus requirements for the taxation of non-residents' business income enshrined in the current rules of international tax law and provides a proposal that is more aligned with international tax policy benchmarks.